A SARS-CoV-2 nanobody that can bind to the RBD region may be used for treatment in COVID-19 in animals. (July 2022) - Wu, Peng; Yang, Qin; Zhao, Xiaoli; Liu, Qingqing; Xi, Jing; Zhang, Fan; He, Jinke; Yang, Hang; Zhang, Chao; Ma, Zhongchen; Deng, Xiaoyu; Wang, Yong; et al.
Abstract: Coronavirus disease 2019 (COVID-19) caused by an infectious virus, severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2), poses a threat to the world. The suitable treatments must be identified for this disease in animals. Nanobody have therapeutic potential in the COVID-19. In this study, SARS-CoV-2 Spike RBD protein was used to make the nanobody. Nanobodies binding to the SARS-CoV-2 Spike RBD protein was obtained. Interestingly, the nanobody could bind to SARS-CoV-2 Spike S protein and RBD protein at the same time. Nanobodies were validated with a neutralizing antibody detection kit. The use of pseudoviruses confirmed that nanobodies could prevent pseudoviruses from infecting cells. We believe the nanobody are very valuable and could be used in the treatment of COVID-19. SARS-CoV-2 nanobodies can be rapidly mass-produced from microorganisms to block SARS-CoV-2 infection in vitro and in vivo with preventive and therapeutic effects. Highlights: Nanobodies with the potential to prevent and treat COVID-19 disease in animals were obtained. The SARS-CoV-2 nanobody could bind to SARS-CoV-2 spike S protein and Spike RBD protein at the same time. The nanobodies could prevent SARS-CoV-2 pseudoviruses from entering cells.